Safety of nicotinamide riboside chloride as a novel food pursuant to Regulation (EU) 2015/2283 and bioavailability of nicotinamide from this source, in the context of Directive 2002/46/EC. (7th August 2019) - ,; Turck, Dominique; Castenmiller, Jacqueline; de Henauw, Stefaan; Hirsch‐Ernst, Karen Ildico; Kearney, John; Maciuk, Alexandre; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Pelaez, Carmen; Pentieva, Kristina; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Allergens (NDA) was asked to deliver an opinion on nicotinamide riboside chloride as a novel food (NF) pursuant to Regulation (EU) 2015/2283, including an evaluation of the safety of its use in food supplements as a source of niacin, and the bioavailability of nicotinamide from this source, in the context of Directive 2002/46/EC. The NF, a synthetic form of nicotinamide riboside, is proposed to be used in food supplements for the healthy adult population at levels up to 300 mg/day. The production process, composition, specifications, batch‐to‐batch variability and stability of the NF do not raise safety concerns. Animal and human data indicate that the NF contributes to the nicotinamide body pool. There are no concerns regarding genotoxicity. Human studies do not raise safety concerns. The proposed maximum use level corresponds to an amount of nicotinamide, which is sixfold lower than the tolerable upper intake level (UL) set for adults, excluding pregnant and lactating women. The margin of exposure (MoE) of 70 derived from repeated dose toxicity studies with rats and dogs is considered sufficient for the adult population, excluding pregnant and lactating women. Regarding these two population groups, the MoE of 76 derived from a developmental toxicity study in rats is considered insufficient in the absence of data which could justify accepting a MoE lower than 100. The Panel concludes that the NF is safe under the proposed conditions of use for the healthy adult population, excluding pregnant and lactating women, and that an intake of the NF up to 230 mg/day is safe for pregnant and lactating women. The Panel also concludes that the NF is a source from which nicotinamide, a form of niacin, is bioavailable.